(3Yjhf GdCfHGA aj WHbGJ GdCWHGAs - (3GHf CHj GUjHYI , ehab GdOjf CHh GdYHGS CMeO Hf GdbGSe Hf NdjaI Hf jhfS GdSYOj GdNRQLj,J (B668 (3g` s
(3ChdgG (B:s
(3jHOC HGdHGH GdSGHY s
(3GdfSNI HgG MhGTs
(3GdfUa GdKGfis
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B197 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B47 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B96s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B218 s
Keywords: (3GdJGQjNs